Ofícios da cidadania como forma de efetivação dos direitos da personalidade: limites e potencialidades do cenário global ao brasileiro - Cigana, Paula Fabíola (2019)
This work studies the Citizenship Offices [office with quality of being democratic] as a way of effectiveness of the personality rights, analyzing the limits and potentialities of the global and Brazilian scenarios, based on the study of doctrine, jurisprudence and international and national regulations, especially the Law No. 13.484/17, which created the Citizenship Offices in Brazil. The specific objectives are: to contextualize the Citizenship Offices in Brazil, their limits and potentialities, based on a research of doctrine, jurisprudence and national legislation, as well as through a comparative study of related legislation; to reflect on the crisis of representation of the traditional State and the possible ways to exercise a democratic citizenship under the cosmopolitan bias; to investigate the potentiality of the Citizenship Offices in the personality fundamental rights protection from the expansion of their functions, based on a doctrinal, legal and jurisprudential study. From this perspective, this works seeks to solve the following research problem: what are the limits and potentialities of Citizenship Offices as an instrument for effectiveness of fundamental rights and guarantees, based on the analysis of limits and perspectives in the Brazilian scenario? In order to answer this question, the hypothetical-deductive method of approach is used, since the work started from the perception of a gap in the knowledge about the role played by the Citizenship Offices in the tutelage and effectiveness of the personality rights. In this context, hypotheses about the limits and possibilities of actuation of Citizenship Offices are studied, in order to test the prediction of the occurrence of phenomena covered by the hypothesis through the process of deductive inference. Finally, it is concluded that the panorama is extremely favorable as far as the possibilities of acting of the Citizenship Offices are concerned, due to a legal opening to the expansion of their functions, along with a normative tendency of the Brazilian National Council of Justice, that each day allows the exercise of more attributions directly to the Extrajudicial Offices.